On the application of the rank tests for nonlinear cointegration to PPP: The case of Papua New Guinea - Liew, Venus Khim-Sen; Ling, Tai-Hu; Chia, Ricky Chee-Jiun; Yoon, Gawon (North-Holland, 2012)
Much interest has been paid recently to the nonlinear cointegrating relations existing among economic variables. Various testing procedures are already available to test for the existence of nonlinear cointegration. For example, Breitung (2001) proposes rank tests and his testing procedure has been broadly applied. In this study, we warn against a blind application of the rank cointegration tests, particularly to economic variables that evidence certain behavior. As an illustration, we employ the nominal exchange rates and relative prices of Papua New Guinea against her major trading partners with the objective of testing the validity of purchasing power parity for the country. Our simulation results also confirm our warnings. Additionally, we provide some simple solutions to the problem we encounter herein.